Role of environmental filtering and functional traits for species coexistence in a harsh tropical montane ecosystem. (1st March 2021) - Tameirão, Lucas B S; Caminha-Paiva, Dario; Negreiros, Daniel; Veloso, Maria Das Dores M; Berbara, Ricardo L L; Dias, Luiz Eduardo; Pierce, Simon; Fernandes, G Wilson
Abstract: Environmental filtering and niche differentiation are often invoked to explain species coexistence at local scales. The ironstone campo rupestre of Brazil provides a biodiverse natural experiment in which edaphic gradients represent filters to test the hypothesis that plant community functional composition, despite converging on extreme stress tolerance, exhibits a co-structure with environmental parameters. At the Serra do Rola-Moça State Park, soil physico-chemical parameters were characterized alongside community-weighted mean plant functional traits and Grime's competitor, stress-tolerator and ruderal strategies for species at each sampling site. In general, species exhibited a high degree of stress tolerance (between 72.6% and 100%), while ruderalism was 0% for all species. Soil nutrients related to plant metabolism (e.g. P, Ca, Mg) were associated with the stress-tolerant strategy and with traits involved in the leaf economics and size spectra. Despite a major edaphic filter selecting stress tolerance, fine-scale microhabitat variability represented by soil parameters related to fertility (i.e. P, Ca, Mg) and water retention capacity (i.e. clay content) was associated with subtle variation in ecological strategies and functional traits of species in the ironstone campo rupestre .